HUBUNGAN PERSONAL HYGIENE DAN SANITASI LINGKUNGAN TERHADAP SKABIES DI PONDOK PESANTREN NURUL ISLAM SEKARBELA - Tita Aprinaya Andika; Fahriana Azmi; Nisia Putri Rinayu; Wiwin Mulianingsih (Nusantara Hasana Journal, 2023)
Scabies is a skin disease caused by Sarcoptes scabiei Var hominis. Conditions that can cause skin infections and are also very disturbing to sufferers. The research objective was to determine the relationship between personal hygiene and environmental sanitation against scabies at the Nurul Islam Sekarbela Islamic Boarding School. The research method is a quantitative analytic observational study with the research design used is a cross sectional study. The sampling technique used purposive sampling. The research was conducted at the Nurul Islam Sekarbela Islamic Boarding School. The research sample is 86 respondents. The data obtained were analyzed by Chi-square test. The significance value limit was (p-value <0.02). In the bivariate analysis, the p-value was 0.00 (p-value <0.02). Conclusion There is a significant relationship between personal hygiene and environmental sanitation on scabies at the Nurul Islam Sekarbela Islamic Boarding School.